Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

integral e^2x/ 9+e^4x, finding the indefinite integral

Sagot :

The given integral expression is :

[tex]\int \frac{e^{2x}}{9+e^{4x}}dx[/tex]

Apply u-substitution method :

[tex]\begin{gathered} \text{Let u = e}^{2x} \\ \text{Differentiate with respect x} \\ \frac{du}{dx}=2e^{2x} \\ du=2e^{2x}dx \\ \frac{du}{2}=e^{2x}dx \\ \text{ So, substitute }e^{2x}dx\text{ = }\frac{du}{2}\text{ and u = e}^{2x}\text{ in the given integral } \end{gathered}[/tex]

Thus the integral become :

[tex]\begin{gathered} \int \frac{e^{2x}}{9+e^{4x}}dx=\int \frac{e^{2x}}{9+e^{2x}e^{2x}}dx \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\int \frac{1^{}}{9+u\cdot u^{}}\frac{du}{2} \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{2}\int \frac{1^{}}{9+u^2^{}}du \end{gathered}[/tex]

Apply the integral substitution : u = 3v

[tex]\begin{gathered} u\text{ =3v} \\ \text{differentiate : du =3dv} \\ \text{substitute the value :} \end{gathered}[/tex]

[tex]\begin{gathered} \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{2}\int \frac{1^{}}{9+u^2^{}}du \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{2}\int \frac{3dv}{9+(3v)^2} \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{2}\int \frac{3dv}{9+9v^2} \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{2}\int \frac{3dv}{9(1+v^2)} \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{2}\int \frac{dv}{3(1+v^2)} \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\int \frac{dv}{(1+v^2)} \end{gathered}[/tex]

Apply the integral expression :

[tex]\int \frac{dx}{1+x^2}=\arctan x[/tex]

So, the expression will be :

[tex]\begin{gathered} \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\int \frac{dv}{(1+v^2)} \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\arctan (v)+C \end{gathered}[/tex]

substitute the value of v = u/3

[tex]\begin{gathered} \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\arctan (v)+C \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\arctan (\frac{u}{3})+C \end{gathered}[/tex]

Now, substitute u = e^2x

[tex]\begin{gathered} \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\arctan (\frac{u}{3})+C \\ \int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\arctan (\frac{e^{2x}}{3})+C \end{gathered}[/tex]

Answer :

[tex]\int \frac{e^{2x}}{9+e^{4x}}dx=\frac{1}{6}\arctan (\frac{e^{2x}}{3})+C[/tex]